ChemInform Abstract: ZrCl2 (η‐C5Me5)2‐AlHCl2· (THF)2: Efficient Hydroalumination of Terminal Alkynes and Cross‐Coupling of the Derived Alanes. Issue 25 (3rd June 2013) - Andrews, Philip; Latham, Christopher M.; Magre, Marc; Willcox, Darren; Woodward, Simon
Abstract Stabilized AlHCl2·(THF)2 hydroaluminates terminal alkynes with excellent chemo‐, regio‐, and stereoselectivity.